Feed Efficiency and Growth Performance in Thai Beef Cattle Fed Cricket Meal as a Soybean Meal Replacement - Benjamad Khonkhaeng; Metha Wanapat; Sarong So; Areerat Lunpha; Ruangyote Pilajun; Pin Chanjula; Pichad Khejornsart; Pongsatorn Gunun; Nirawan Gunun; Bundit Tengjaroensakul; Sineenart Polyorach; Anusorn Cherdthong (Veterinary Medicine International, 2025)
= 0.02) compared to cattle fed the soybean meal-based diet. These results suggest that cricket meal can serve as a complete replacement for soybean meal in beef cattle diets, enhancing protein digestibility and growth performance without compromising rumen function.
Keywords: Insect Utilization and Effects; Insect and Arachnid Ecology and Behavior; Animal and Plant Science Education